2010
DOI: 10.1007/s10554-010-9671-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and role of early cardiac magnetic resonance imaging in patients with suspected ST-elevation myocardial infarction and normal coronary arteries

Abstract: A variety of conditions other than acute myocardial infarction may cause ST-elevation. Our objective was to evaluate the impact of cardiac magnetic resonance (CMR) on differential diagnosis from a prospective series of patients with suspected ST-elevation myocardial infarction (STEMI) and completely normal coronary arteries. Among 1,145 patients with suspected STEMI, 49 patients had completely normal coronary arteries and entered a prospective registry. CMR was done within 24 h, if possible, and included funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 25 publications
(30 reference statements)
0
46
1
7
Order By: Relevance
“…However, despite an increasing interest, there have been few studies of MINCA, hence the prevalence remains uncertain. It was recently reported that approximately 4% of all patients with suspected myocardial infarction may have angiographically normal coronary arteries [1], whereas we have reported an incidence of 7% [2]. Because myocarditis may mimic myocardial infarction, it is essential to exclude this condition in patients with MINCA.…”
Section: Introductionmentioning
confidence: 70%
“…However, despite an increasing interest, there have been few studies of MINCA, hence the prevalence remains uncertain. It was recently reported that approximately 4% of all patients with suspected myocardial infarction may have angiographically normal coronary arteries [1], whereas we have reported an incidence of 7% [2]. Because myocarditis may mimic myocardial infarction, it is essential to exclude this condition in patients with MINCA.…”
Section: Introductionmentioning
confidence: 70%
“…9 However, increasing evidence suggests that CMR may provide incremental diagnostic value in these patients. [10][11][12][13] We have adopted CMR in the diagnostic work-up of patients with suspected ACS.…”
mentioning
confidence: 99%
“…[20][21][22][27][28][29] Prior studies using CMR perfusion imaging in patients with acute coronary syndrome and nonobstructive CAD did not include stress testing. [16][17][18][19]30,31 Adenosine stress perfusion CMR is highly sensitive, specific, and reproducible for identification of obstructive CAD and has been reported to be superior to other stress imaging methods for this purpose. [32][33][34][35][36][37][38] In the setting of stable, nonobstructive CAD, patients with proven microvascular disease based on invasive coronary reactivity testing had lower MPRI as compared with healthy controls.…”
Section: Cmr Evidence Of Infarction (Lge)mentioning
confidence: 99%
“…13 Advanced imaging modalities, including intravascular imaging and cardiac magnetic resonance imaging (CMR), may help to characterize MI etiology in these patients. [14][15][16][17][18][19] Microvascular coronary disease is a known cause of chest pain with nonobstructive CAD. 20 Abnormal coronary flow reserve is a predictor of adverse outcomes, including death, in stable patients with nonobstructive CAD.…”
Section: Introductionmentioning
confidence: 99%